Dragon ball the complete illustrations. Featuring the artwork from Dragon Ball and Dragon Ball Z - Toriyama, Akira 1955-2024 (VIZ Media, 2008)
Presents the illustrations from the manga "Dragonball," spanning 1984-1995, and an interview with artist Akira Toriyama
Originally published: Japan : Shūeisha, c1995.
Keywords: Toriyama, Akira / 1955- / Doragon Bōru / Illustrations; Toriyama, Akira -- 1955-2024; Toriyama, Akira -- 1955-2024 -- Doragon bōru; Comic strip characters / Japan; Comic books, strips, etc / Japan; Interview